Morfologia e grânulos citoplasmáticos do corpo lúteo da vaca anelorada (Bos taurus indicus) gestante e não gestante - Laura Ribeiro Vargas (2014)
The purpose of this study was to evaluate the volumetric proportion of the corpus luteum, the mean nuclear diameter of lutein cells and the distribution of lutein cells with cytoplasmic granules in the corpus luteum throughout pregnancy, and in cyclic Nelore cows. Twenty four ovaries with corpus luteum were collected in Santa Vitória slaughterhouse (Contagem-MG). The ovaries were divided into four groups of six: animals until 90 days of pregnancy (1st third), animals with gestation between 91 and 180 days (2nd third), animals with gestation between 181 and 270 days (3rd third) and cyclic animals. The corpus luteum were processed for inclusion in paraplast. The tissues were stained in Hematoxilin-eosin, Gomoris Trichrome, Toluidine blue, Bromophenol blue and Xylidine Ponceau for analysis in light microscope. In volumetric proportion the constituents analyzed were: lutein cells cytoplasm and nucleus, connective tissue and fibroblasts, endothelial cells and pericyte and blood vessels. The frequency of corpus luteum in the right ovary was 79,16% (19/24). The volumetric proportion of lutein cells cytoplasm decreased from 46,13±2,84% to 37,88±3,50% and the volumetric proportion of nucleus descreased from 9,16±1,03% to 6,21±1,02% between the frist and the second third of pregnancy. The amount of connective tissue and fibroblasts significantly increased throughout gestation, with 20,93±5,39% on first third and 34,04±4,17% on second. An increase in the nuclear diameter of large lutein cells was observed between first (23,66±1,73%) and last third (26,27±1,33%) of pregnancy, and the nuclear diameter of small lutein cells was not different between groups. Cytoplasmic granules were found only in the large luteal cells. The amount of lutein cells with granules increased throughout gestation, but significant difference was observed only between the first (2,33±1,94%) and second third (25,50±20,34%).